Chlorpromazine Induced Cataract in a female patient: A Case Report - Thapa, Nidhi Rajeshwori; Karki, Deepika; Shrestha, Asim; Singh, Pradip Man (Journal of Psychiatrists’ Association of Nepal, 2022)
Tablet Chlorpromazine is a commonly used, affordable antipsychotic in developing countries. Chlorpromazine induced cataract and corneal pigmentation was first described by Greiner & Berry in 1964 but in the context of Nepal, there is no available literature or cases reported to date. Despite having a myriad of side effects, it is still used frequently in developing countries due to its cost-effectiveness. In this light, we report a case of a 43-year-old female with a diagnosis of Schizophrenia who had been treated with Tab. Chlorpromazine for 25 years. She lost to follow-up and presented at the OPD with cataract in bilateral eyes.